Using Offensive Words as Unethical Advertising in Viral Marketing at Angkringan West Semarang - Helga Hosea Ravanda; Devi Purnamasari (Syntax Corporation Indonesia, 2023)
Communication strategy is the main factor for doing marketing. Likewise, what was conducted by Angkringan West in order to increase the number of followers and customers in its culinary business, a communication strategy was chosen using offensive words which were considered controversial. The purpose of this study was to analyze the marketing communication strategy concept of the owner of Angkringan West interested in using offensive words in conducting marketing communications, to analyze the considerations and the expected impact of using offensive words as unethical advertising on Angkringan West. This research was conducted using a type of qualitative research. As for the results of the study, it was found that 1) the consideration of using offensive words was adapted to use the language of social communication, namely the Semarangan language which flows spontaneously; 2) choosing the strategy of using offensive words is not to cause discomfort, impolite or unethical in trading, but the acceptance of offensive words depends on the demographics of the audience and the willingness to join the Angkringan West community. Conclusion: offensive words are an appropriate marketing strategy to use with certain marketing targets.